Discourses on sustainable forest management in the Caatinga Domain - Lucena, Marcelo Silva De [UNESP]; Zakia, Maria José Brito [UNESP]; Guerin, Natalia [UNESP] (ANPPAS - Revista Ambiente e Sociedade, 2024)
Sustainable forest management (SFM) can harbor different discourses on sustainability. In this paper, based on discourse theory, the main ideas, concepts and narratives that have been proposed about the SFM of the native vegetation of the Caatinga Domain (DC) were characterized. Three main speeches were highlighted: a) Bioenergetic SFM: emphasizes the production of forest biomass to supply regional energy demands; additionally, it seeks to contribute strongly to the reduction of deforestation and forest conservation; b) Silvopastoral SFM: seeks to offer alternatives to improve forage availability; c) Non-timber SFM: seeks to value traditional knowledge about biodiversity, to expand the ways of managing multiple species and strengthen strategies for coexistence with the semi-arid region. The existence of different discourses, together with the range of sustainable practices they present, offers the opportunity for policy change and institutional innovation.

El manejo forestal sostenible (MFS) puede albergar diferentes discursos sobre la sostenibilidad. En este trabajo, basado en la teoría del discurso, se caracterizaron las principales ideas, conceptos y narrativas que se han propuesto sobre lo MFS de la vegetación nativa del Dominio de la Caatinga (DC). Se encontraron tres discursos principales: a) MFS bioenergético: enfatiza la producción de biomasa forestal para abastecer las demandas energéticas regionales; además, busca contribuir fuertemente a la reducción de la deforestación y la conservación de los bosques; b) MFS silvopastoril: busca proporcionar alternativas para mejorar la disponibilidad forrajera; c) MFS no maderable: busca valorar los conocimientos tradicionales sobre la biodiversidad, ampliar las formas de manejo de múltiples especies y fortalecer las estrategias de convivencia con el semiárido. La existencia de diferentes discursos, junto con la gama de prácticas sostenibles que presentan, ofrece la oportunidad para el cambio de políticas y la innovación institucional.
Discursos sobre manejo forestal sostenible en el Dominio Caatinga
Keywords: Forest discourse; bioenergy; Silvopastoral systems; non-timber products; sustainability